Oral Modified Release Multiple-Unit Particulate Systems: Compressed Pellets, Microparticles and Nanoparticles - Nihad Al-Hashimi; Nazish Begg; Raid G. Alany; Hany Hassanin; Amr Elshaer (MDPI AG, 2018)
Oral modified-release multiparticulate dosage forms, which are also referred to as oral multiple-unit particulate systems, are becoming increasingly popular for oral drug delivery applications. The compaction of polymer-coated multiparticulates into tablets to produce a sustained-release dosage form is preferred over hard gelatin capsules. Moreover, multiparticulate tablets are a promising solution to chronic conditions, patients’ adherence, and swallowing difficulties if incorporated into orodispersible matrices. Nonetheless, the compaction of multiparticulates often damages the functional polymer coat, which results in a rapid release of the drug substance and the subsequent loss of sustained-release properties. This review brings to the forefront key formulation variables that are likely to influence the compaction of coated multiparticulates into sustained-release tablets. It focusses on the tabletting of coated drug-loaded pellets, microparticles, and nanoparticles with a designated section on each. Furthermore, it explores the various approaches that are used to evaluate the compaction behaviour of particulate systems.